Perception of cultured “meat” by Italian, Portuguese and Spanish consumers - Liu, Jingjing; Almeida, João M.; Rampado, Nicola; Panea, Begoña; Hocquette, Élise; Chriki, Sghaier; Ellies-Oury, Marie-Pierre; Hocquette, Jean-Francois (Frontiers in Nutrition, 2023)
The aim of this study was to investigate how consumers from southwestern Europe perceive cultured “meat” (CM) and whether demographic characteristics (origin, gender, age, education, occupation and meat consumption) are related to their willingness to try (WTT), eat regularly (WTE) and pay (WTP) for CM. We found that the current respondents seem to have a fairly positive attitude towards CM, 49% of them perceived CM as “promising and/or acceptable” and 23% “fun and/or intriguing” whereas 29% considered it “absurd and/or disgusting”. In total, 66% and 25% would be willing and not willing to try CM respectively, but 43% have no WTE CM and, 94% would not pay more for CM compared to conventional meat. Age and especially occupation may be good indicators of consumer acceptance of CM. Respondents between 18-30 years of age are the most accepting. Respondents outside the meat sector have the highest WTE and those working in the meat sector have the lowest WTE, scientists (within or outside the meat sector) have the highest WTT, non-scientists but in the meat sector have the lowest WTT. Additionally, we found that men are more likely to accept CM than women, Spanish-speaking consumers have the highest WTT and WTE, people with vegan and vegetarian diets may pay more for CM but generally not more than for conventional meat. The perceptions that CM may be more eco-friendly, ethical, safe and healthy than conventional meat, and to a lesser extent, the perception that current meat production causes ethical and environmental problems are likely to be major motives for the current respondents to try, eat regularly and pay for CM. In contrast, lower perceptions of the benefits of CM and the weaknesses of conventional meat, plus emotional resistance towards CM, are the main barriers to acceptance of CM.